Association of Epstein-Barr virus (EBV) with Solid Tumors - Lima, Marcos Antonio Pereira de (2006)
The gamma-herpes Epstein-Barr virus (EBV) is a ubiquitous viral agent that causes persistent infection in more than 90% of the world adult population. EBV is associated with several lymphoproliferative disorders such as infectious mononucleosis, Burkitt's lymphoma, Hodgkin's disease, and post-transplant lymphoproliferative disease. The oncogenic role of EBV in tumors of lymphoid origin has been widely investigated. With respect to solid tumors, the role of EBV is well documented in nasopharyngeal carcinoma. However, new findings have shown that the spectrum of cellular infection of EBV is broader, having been detected in cells from other kinds of solid tumors, thus indicating its involvement in tumorigenesis of these tumors. The current article begins with a brief description of EBV biology and aims to provide a summary of new findings concerning the association between EBV and solid tumors, highlighting evidence of the viral role and characteristics of infections in each tissue.